General practitioner well-being during the COVID-19 pandemic: a qualitative interview study - Karen Bloor; Laura Jefferson; Claire Heathcote (BMJ Open, 2023)
Objectives The COVID-19 pandemic presented new challenges for general practitioners’ (GPs’) mental health and well-being, with growing international evidence of its negative impact. While there has been a wide UK commentary on this topic, research evidence from a UK setting is lacking. This study sought to explore the lived experience of UK GPs during COVID-19, and the pandemic’s impact on their psychological well-being.Design and setting In-depth qualitative interviews, conducted remotely by telephone or video call, with UK National Health Service GPs.Participants GPs were sampled purposively across three career stages (early career, established and late career or retired GPs) with variation in other key demographics. A comprehensive recruitment strategy used multiple channels. Data were analysed thematically using Framework Analysis.Results We interviewed 40 GPs; most described generally negative sentiment and many displayed signs of psychological distress and burnout. Causes of stress and anxiety related to personal risk, workload, practice changes, public perceptions and leadership, team working and wider collaboration and personal challenges. GPs described potential facilitators of their well-being, including sources of support and plans to reduce clinical hours or change career path, and some described the pandemic as offering a catalyst for positive change.Conclusions A range of factors detrimentally affected the well-being of GPs during the pandemic and we highlight the potential impact of this on workforce retention and quality of care. As the pandemic progresses and general practice faces continued challenges, urgent policy measures are now needed.